Discovery of non-boronic acid Arginase 1 inhibitors through virtual screening and biophysical methods. (15th March 2023) - Gathiaka, Symon; Palte, Rachel L.; So, Sung-Sau; Chai, Xiaomei; Richard Miller, J.; Kuvelkar, Reshma; Wen, Xiujuan; Cifelli, Steven; Kreamer, Anthony; Liaw, Andy; McLaren, David G.; Fischer, Christian
Graphical abstract: Abstract: Inhibiting Arginase 1 (ARG1), a metalloenzyme that hydrolyzes l -arginine in the urea cycle, has been demonstrated as a promising therapeutic avenue in immuno-oncology through the restoration of suppressed immune response in several types of cancers. Most of the currently reported small molecule inhibitors are boronic acid based. Herein, we report the discovery of non-boronic acid ARG1 inhibitors through virtual screening. Biophysical and biochemical methods were used to experimentally profile the hits while X-ray crystallography confirmed a class of trisubstituted pyrrolidine derivatives as optimizable alternatives for the development of novel classes of immuno-oncology agents targeting this enzyme.